The first century of railway infrastructure in the North of Minas Gerais: process deployment, boom, crisis and grant - Pereira, Luiz Andrei Gonçalves (2012)
In the policy expansion of railway infrastructure in Brazil, the region “norte-mineira” was included in two major projects of national integration, through the railroad system. The first, connecting the national capital, Rio de Janeiro, Belém in Pará state, passing the river San Francisco. The second, linking the city of Rio de Janeiro to Salvador, passing Montes Claros, in Minas Gerais state. This paper aims to analyze the process of expansion of railway infrastructure in the region north of Minas Gerais in the period 1908 to 2009, considering the historical aspects, following the period of emergence, boom, crisis and grant of the rail system. The study was developed through literature, documentary research and data collection from secondary sources close to government institutions. The shares of public companies railways, among them the railroad of Iron Central of Brazil and the Federal Railroad Company East of Brazil, had an important role in the development of railways, mainly in the north of Minas Gerais. The arrival of the rails resulted in the expansion of existing urban centers, the emergence of new centers and expansion of regional economic activities, including production, trade and movement. In the decade after 1960, the railroad north-mining was a restructuring of the tracks and material spins, seeking to improve the traffic conditions and meet national policy of economic modernization and regional levels. The low investment in rail infrastructure that led to the scrapping, resulting in grants. In 1996 the railroad “norte-mineira” was forwarded to the dealership Ferrovia Centro-Atlantica, which devoted itself exclusively to transport cargo.